Karakteristik morfologi dan fisiologi beberapa isolat lokal bakteri simbiose nematoda entomopatogen kompleks serta uji virulensi pada larva Plutella xylostella - Mardianto Harahap; Didik Sulistyanto (Jurnal Entomologi Indonesia, 2004)
Local isolates of entomopathogenic nematodes are symbiotically associated with bacteria of the genus Xenorhabdus or Photorhabdus. Symbiont bacteria isolated from local isolates of entomopathogenic nematode (Pujon, Cemoro Lawang and X. nematophilus) were identical with Xenorhabdus spp and isolate of Ngadas was identical with Photorhabdus luminescens. Some isolates, such as Xenorhabdus (isolate of Pujon) and P. luminescens (isolate of Ngadas) has a high virulence when the bacteria was injected into insect haemocoel. High virulence was indicated by Xenorhabdus nematophilus when it was applied orally.